An Informatics Benchmarking Statement - Pigott, K.; Lusignan, S. de; Rapley, A.; Robinson, J.; Pritchard-Copley, A. (Methods of Information in Medicine, 2007)
Objectives: Benchmarking statements provide a mechanism for making academic standards explicit within a subject area. They allow comparisons between courses to be based on learning outcomes rather than by defining a curriculum. No such statement has been produced for informatics. In the absence of any established benchmarking statements for informatics a new biomedical informatics course at St. George’s has developed a first benchmarking statement — which defines the skills knowledge and understanding a biomedical informatics student should acquire by the time they completethe course.Methods: Review of national biomedical science and computing subject benchmarking statements and academic educational objectives and national occupational competencies in informatics.Results: We have developed a twenty-item benchmarking statement and this is available on-line at: http://www.gpinformatics.org/benchmark2006/. This benchmarking statement includes a definition and justification for all twenty statements. We found international educational objectives and national informatics competencies useful and these are mapped to each one. National subject benchmarks for computing and biomedical science were less useful and have not been systematically mapped.Conclusions: Benchmarking the skills, knowledge and understanding that a student should acquire during their course of study may be more useful than setting a standard curriculum. This benchmarking statement is a first step towards defining the learning outcomes and competencies a student of this discipline should acquire. The international informatics community should consider moving from a standard curriculum to an agreed subject benchmarking statement for medical, health and biomedical informatics.
Keywords: Benchmarking; informatics; curriculum; educational measurements; learning